Lineage Conflict: Rejection of Feminist Identity Noble Women in The Movie Avatar The Last Airbender 2024 - Rediva Novalisty; Anas Ahmadi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The imbalance in gender recognition between women and men has encouraged the feminist movement which emphasizes the recognition of feminist identity. Feminist identity upholds women's culture and values ​​as distinctive characteristics. However, the feminist movement was not completely successful, women still often live in the shadow of men's expectations. This causes women to abandon their identity and adapt the value of inclusion. The research method is qualitative descriptive using listening and note-taking techniques. The problem related to the depiction of women with the adaptation of masculinity in the film Avatar The Last Airbender focuses on noble female characters. The aim is to describe the representation of rejection of female feminist identity in the character Azula in the film. The research results show that Azula's rejection of her feminist identity is due to her ambition to control the throne and fulfill the expectations of the criteria for a leader given by her father. Azula adapts masculinity values ​​from the way she dresses, her favorite choices which mostly emphasize muscles and strength, her interest in political aspects and warfare, and her aggressive nature. Azula's character is a breakthrough for the stereotype of a noble princess who must be gentle and full of love. On the other hand, Azula emphasizes strength, ambition, and a strong desire to defeat. Keywords: feminist identity, feminism, masculinity